Sound practice in government debt management - Wheeler, Graeme (Washington D.C. : World Bank, 2004)
Modernizing sovereign debt management is paramount for governments in managing volatile capital flows. This book offers valuable insights to assist government policy-makers in understanding what is involved in implementing sound practice in sovereign debt management.
Includes bibliographical references (p. 191-194) and index.
rpm 23/09/16
Loans
Keywords: Debts, Public; Debts, Public -- Management